2022
DOI: 10.5371/hp.2022.34.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Analysis in Asymptomatic COVID-19+ Hip Fracture Patients: Is There an Increase in Mortality?

Abstract: Purpose Mortality rates following hip fracture surgery have been well-studied. This study was conducted to examine mortality rates in asymptomatic patients presenting for treatment of acute hip fractures with concurrent positive COVID-19(+) tests compared to those with negative COVID-19(–) tests. Materials and Methods A total of 149 consecutive patients undergoing hip fracture surgery during the COVID-19 pandemic at two academic medical centers were reviewed retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Finally, we conducted a meta-analysis and systematic review, including 40 eligible studies with 17,753 patients with hip fractures, among which were 2280 patients with COVID-19 (12.8%) [11,. Except for Vialonga et al (2020), all studies had a research period in 2020 [54]. Hall et al (2022) reported the highest number of COVID-19 infections with 651 [36], followed by Rashid et al (2022) with 517 infections [50].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we conducted a meta-analysis and systematic review, including 40 eligible studies with 17,753 patients with hip fractures, among which were 2280 patients with COVID-19 (12.8%) [11,. Except for Vialonga et al (2020), all studies had a research period in 2020 [54]. Hall et al (2022) reported the highest number of COVID-19 infections with 651 [36], followed by Rashid et al (2022) with 517 infections [50].…”
Section: Resultsmentioning
confidence: 99%